Autologous stem cell transplantation in elderly patients (≥60 years) with diffuse large B-cell lymphoma: an analysis based on data in the European Blood and Marrow Transplantation registry - Esa Jantunen; Carmen Canals; Alessandro Rambaldi; Gert Ossenkoppele; Bernardino Allione; Didier Blaise; Eulogio Conde; Hervè Tilly; Gordon Cook; Fiona Clark; Andrea Gallamini; Andrew Haynes; et al. (Haematologica, 2008)
Background There is currently limited experience on the feasibility and efficacy of autologous stem cell transplantation in elderly patients with diffuse large B-cell lymphoma.Design and Methods We analyzed the outcome of 2612 patients with diffuse large B-cell lymphoma treated with autologous stem cell transplantation between 2000 and 2005 and reported to the European Blood and Marrow Transplantation registry. Four hundred and sixty-three patients (18%) were ≥60 years old at the time of the transplant (median, 63 years). When compared to 2149 patients <60 years old at the time of transplantation, the elderly patients had more frequently received at least two treatment lines (76% vs. 57%, p<0.001), were less commonly in first complete remission at the time of transplantation (23 % vs. 30 %, p=0.005) and received their transplants later after diagnosis (median time 14 months vs.7.5 months, p<0.001).Results Non-relapse mortality was higher in elderly patients at 100 days (4.4 % vs. 2.8 %), at 1 year (8.7% vs. 4.7%) and at 3 years (10.8% vs. 6.5%) (p=0.002). With a median follow-up of 12 months for the surviving patients for the elderly group and 15 months for the younger group, the risk of relapse was 38% and 32%, respectively (p=0.006).The progression-free survival was 51% and 62%, respectively, at 3 years (p<0.001). The overall survival rate was 60% vs. 70%, respectively, at 3 years (p<0.001).Conclusions Autologous stem cell transplantation is feasible in selected elderly patients with diffuse large B-cell lymphoma, although non-relapse mortality is somewhat higher than in younger patients. Both progression-free and overall survival rates are promising taking into account the generally poorer outcome of elderly patients with diffuse large B-cell lymphoma.